Galectin-1: A Jack-of-all-trades in the resolution of acute and chronic inflammation - Sundblad, Victoria (2017)
Regulatory signals provide negative input to immunologicalnetworks promoting resolution of acute andchronic inflammation. Galectin-1 (Gal-1), a member of afamily of evolutionarily conserved glycan-binding proteins,displays broad anti-inflammatory and proresolvingactivities by targeting multiple immune cell types. Withinthe innate immune compartment, Gal-1 acts as a resolutionassociatedmolecular pattern by counteracting the synthesisof proinflammatory cytokines, inhibiting neutrophiltrafficking, targeting eosinophil migration and survival,and suppressing mast cell degranulation. Likewise, thislectin controls T cell and B cell compartments by modulatingreceptor clustering and signaling, thus serving asa negative-regulatory checkpoint that reprograms cellularactivation, differentiation, and survival. In this review,we discuss the central role of Gal-1 in regulatoryprograms operating during acute inflammation, autoimmunediseases, allergic inflammation, pregnancy, cancer,and infection. Therapeutic strategies aimed at targetingGal-1?glycan interactions will contribute to overcomecancer immunosuppression and reinforce antimicrobialimmunity, whereas stimulation of Gal-1?driven immunoregulatorycircuits will help to mitigate exuberant inflammation.